The multicomponent residue depletion of Gelsemium elegans in pig tissues, urine, and plasma - Wu, Yong; Long, Xue-Ming; Liu, Gao-Feng; Bai, Xia; Sun, Zhi-Liang; Liu, Zhao-Ying (Frontiers in Veterinary Science, 2023)
Introduction: Gelsemium elegans (G. elegans) as a traditional medicinal plant used in livestock production. The use of G. elegans in veterinary clinics may pose safety risks to human health. Objectives: The aim of this study was to investigate tissue residue depletion in pigs fed G. elegans powder. Methods: A precise quantitation method and a simultaneous semi-quantitation method for multiple components independently of standards in pig tissues were developed for the first time. The two methods were validated in terms of specificity, LODs, LOQs, linearity, accuracy, precision, and matrix effects. They were then applied to a tissue residue depletion study after G. elegans powder at a dose of 2% per kg feed were fed to pigs. Results: Compared with precise quantitation, the method validation results indicated that the semi-quantitation method was reliable and acceptable for multicomponent quantification independent of standards. Many G. elegans alkaloids are widely distributed in most tissues of pigs. Tissue residue depletion studies indicated that 14-hydroxygelsenicine, 11-hydroxygelsenicine, and gelsemoxonine could be used as potential residue markers, and pancreas, small intestine, and lung tissues could be considered as potential residue target tissues of G. elegans. In addition, both urine and plasma could be used to predict 14-hydroxygelsenicine and gelsemoxonine residues in the liver, pancreas, and small intestinal tissues of pigs. Conclusion: The developed semi-quantification method can be applied to monitor the application and residue of G. elegans. The results provide scientific evidence for evaluating the safety of animal-derived food from G. elegans for consumers and will be helpful for its application and future development.